Determination of kinetics of CO2 absorption in solutions of 2‐amino‐2‐methyl‐1‐propanol using a microfluidic technique. Issue 12 (22nd August 2015) - Zheng, Chen; Zhao, Bochao; Wang, Kai; Luo, Guangsheng
Abstract : The kinetics for the reactions of carbon dioxide with 2‐amine‐2‐methyl‐1‐propanol (AMP) and carbon dioxide (CO2 ) in both aqueous and nonaqueous solutions were measured using a microfluidic method at a temperature range of 298–318 K. The mixtures of AMP‐water and AMP‐ethylene glycol were applied for the working systems. Gas‐liquid bubbly microflows were formed through a microsieve device and used to determine the reaction characteristics by online observation of the volume change of microbubbles at the initial flow stage. In this condition, a mathematical model according to zwitterion mechanism has been developed to predict the reaction kinetics. The predicted kinetics of CO2 absorption in the AMP aqueous solution verified the reliability of the method by comparing with literatures' results. Furthermore, the reaction rate parameters for the reaction of CO2 with AMP in both solutions were determined. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4358–4366, 2015